Green synthesis of yellow emitting PMMA–CdSe/ZnS quantum dots nanophosphors. (November 2015) - Mohan, Sneha; Oluwafemi, Oluwatobi S.; Songca, Sandile P.; George, Soney C.; Miska, Patrice; Rouxel, Didier; Kalarikkal, Nandakumar; Thomas, Sabu
Abstract: We herein report the fabrication of highly fluorescent yellow emitting nanophosphors using CdSe/ZnS quantum dots (QDs) dispersed in polymethyl methacrylate (PMMA). The QDs were synthesised via a simple, non-phosphine and one pot synthetic method in the absence of an inert atmosphere. The as-prepared nanocrystallites were characterised by Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible (UV–vis) and photoluminescence spectroscopy, energy-dispersive spectroscopy (EDS), Raman spectroscopy, transmission electron microscopy (TEM) and high resolution TEM (HRTEM) microscopy. Optical analysis confirmed that the as-synthesised CdSe/ZnS QDs were of high quality with sharp absorption peaks, bright luminescence, narrow emission width and high PL quantum yield (up to 74%). The electron microscope images showed that the QDs are small and spherical in shape with narrow size distributions while the HRTEM micrograph confirmed the high crystallinity of the material. The Raman analysis of the QDs revealed the formation of core–shell structure and the energy dispersive spectroscopy confirmed the presence of the corresponding elements (i.e., Cd, Se, Zn and S). The dispersion of the core–shell QDs in PMMA matrix led to the red-shifting of the emission position from 393 nm in the neat PMMA to 592 nm in the nanocomposite. The fabricated highly fluorescent yellow emitting PMMA–CdSe/ZnS core–shell QDs polymer nanocomposite film display excellent optical properties without loss of luminescence. Furthermore, the as-synthesised organic soluble CdSe/ZnS QDs were successfully converted into highly water soluble QDs after ligand exchange with mercaptoundecanoic acid (MUA) without the loss of their emission properties. The simplicity of the method and the quality of the as-synthesised nanocomposite make it a promising material for the large scale fabrication of diverse optical devices.